Proof-of-concept study of compartmentalized lung ventilation using system for asymmetric flow regulation (SAFR) - Barjaktarevic, Igor; Meyerowitz, Glen; Williams, Onike; Emeruwa, I. Obi; Hoftman, Nir (Frontiers in Medical Technology, 2023)
Asymmetrical distribution of acute lung injury in mechanically ventilated patients can result in a heterogeneity of gas distribution between different regions, potentially worsening ventilation-perfusion matching. Furthermore, overdistension of healthier, more compliant lung regions can lead to barotrauma and limit the effect of increased positive end-expiratory pressure (PEEP) on lung recruitment. We propose a System for Asymmetric Flow Regulation (SAFR) which, combined with a novel double lumen endobronchial tube (DLT) may offer individualized lung ventilation to the left and right lungs, better matching each lung’s mechanics and pathophysiology. In this preclinical experimental model, the performance of SAFR on gas distribution in a two-lung simulation system was tested. Our results indicate that SAFR may be technically feasible and potentially clinically useful although further research is warranted.